ผลการจัดกิจกรรมเคลื่อนไหวเชิงพิลาทีสที่มีต่อพัฒนาการด้านร่างกายของเด็กปฐมวัย - สร้อยเสนา, สุวรรณี; ภิญโญอนันตพงษ์, สิริมา (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2016)
THE EFFECT OF PILATES MOVEMENT ACTIVITY ON PHYSICAL DEVELOPMENT OF PRESCHOOL CHILDREN การวิจัยครั้งนี้มีจุดมุ่งหมายเพื่อศึกษาระดับและการเปลี่ยนแปลงพัฒนาการด้านร่างกายโดยรวมและรายทักษะของเด็กปฐมวัยที่เกิดจากการจัดกิจกรรมเคลื่อนไหวเชิงพิลาทีส กลุ่มตัวอย่างที่ใช้ในการศึกษาครั้งนี้เป็นนักเรียนชาย - หญิง อายุระหว่าง 3 - 4 ปี ชั้นอนุบาลปีที่ 1 ภาคเรียนที่ 2 ปีการศึกษา 2557 โรงเรียนคลองขวาง ตำบลท่ากุ่ม อำเภอเมืองตราด จังหวัดตราด ซึ่งได้มาโดยวิธีการเลือกแบบเจาะจง 1 ห้องเรียนและจับสลากเด็ก จำนวน 20 คน ใช้เป็นกลุ่มทดลองเพื่อจัดกิจกรรมเคลื่อนไหวเชิงพิลาทีสเป็นเวลา 8 สัปดาห์สัปดาห์ละ 4 วัน วันละ 25 นาที เครื่องมือที่ใช้ในการวิจัยคือ แผนการจัดกิจกรรมเคลื่อนไหวเชิงพิลาทีสและแบบทดสอบเชิงปฏิบัติพัฒนาการด้านร่างกายที่ผู้วิจัยสร้างขึ้น ซึ่งมีค่าความเชื่อมั่นทั้งฉบับเท่ากับ .80 ในการวิจัยครั้งนี้ใช้แบบแผนการทดลองแบบ One-Group Pretest-Posttest Design และสถิติที่ใช้ในการวิเคราะห์ข้อมูล คือ t-test แบบ Dependent Samples ผลการวิจัยพบว่า เด็กปฐมวัยที่ได้รับการจัดกิจกรรมเคลื่อนไหวเชิงพิลาทีสก่อนและหลังการทดลอง มีระดับคะแนนพัฒนาการด้านร่างกายแตกต่างกันอย่างมีนัยสำคัญทางสถิติที่ระดับ p<.01 ทั้งโดยรวม ( = 17.10, t = 20.48) และรายทักษะ คือ ทักษะการเดิน ( = .81, t = 14.91) ทักษะการยืน ( = .72, t = 11.53) ทักษะการกระโดด ( = .92,t = 12.90) โดยการจัดกิจกรรมเคลื่อนไหวเชิงพิลาทีสส่งผลต่อพัฒนาการด้านร่างกายโดยรวมร้อยละ 79(EI = .79) และรายทักษะคือ ทักษะการเดินร้อยละ 73 (EI = .73) ทักษะการยืนร้อยละ 80 (EI = .80) และทักษะการกระโดดร้อยละ 85 (EI = .85) ตามลำดับ แสดงว่าการจัดกิจกรรมเคลื่อนไหวเชิงพิลาทีส ช่วยให้พัฒนาการด้านร่างกายของเด็กปฐมวัยโดยรวมและรายทักษะเปลี่ยนแปลงเพิ่มขึ้นอย่างชัดเจน The main purpose of this research was to study the physical development levels and changes of preschool children both in overall and in individual skills through the use of pilates movement activity. The samples used in the study were 4-5 year-preschool boys and girls, who were studying in the frst year preschool at second semester of 2014 academic year at Khlongkhwang School in Thakam Sub-district, Mueang District, Trat Province. One class was selected by purposive sampling and then 20 children were chosen by drawing and used as the experimental group with the use of Pilates movement activity within the period of 8 weeks, 4 days a week, and 25 minutes for each day. The research instruments were the plans for Pilates movement activity and the performance test of physical development with the reliability of the whole paper at .80. The research followed the one group pretest-posttest design and the data were statistically analyzed by using dependent sample t-test. The research results revealed that, before and after the use of Pilates movement activity, the score levels of physical development of preschool children were different with statistical signifcance at the level of p<.01 both in general ( = 17.10, t = 20.48) and in individual areas of walking skill ( = .81, t = 14.91), standing skill ( = .72, t = 11.53) and jumping skill ( = .92, t = 12.90). The Pilates movement activity provided the effects on their physical development in general at 79% (EI = .79) and in individual areas of walking skill at 73% (EI = .73), standing skill at 80% (EI = .80) and jumping skill at 85% (EI = .85), respectively. The results indicated that the Pilates movement activity could obviously improve the changes in physical development of preschool children both in general and in individual skills.